Specifications Framework for Tests in an Outcome-based Language Program - Trang, Hoang Hong; Chi, Nguyen Thi; Mai, Duong Thu (VNU Journal of Foreign Studies, 2016)
Abstract: Driven by the transformation of the language curriculum in the light of the competence-based approach, assessment activities serve as a tool both to measure students’ achievement and to inform their learning progress. As such, it is a requirement that those activities be aligned with targeted competence, or learning outcomes. With broad understanding of outcomes, tests might also be considered as an outcome-based assessment tool, the quality of which can only be assured by a so-called “outcome-based” test spec. This paper, hence, presents various understandings of ‘learning outcomes’, and how testing can be adjusted to fit in with outcome-based assessment. Accordingly, different models of test specifications are reviewed and critiqued, followed by the proposal of a test specification model that is likely to facilitate outcome-based educational system.